EDUKASI GIZI YANG SEHAT UNTUK PENCEGAHAN STUNTING DI KELURAHAN BENDA BARU KECAMATAN PAMULANG TANGERANG SELATAN - Rusilanti; Nur Riska (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2021)
The number of malnutrition in Indonesia is considered high with the results of the Nutrition Status Monitoring conducted by the Indonesian Ministry od Health in 2016, the nutritional status of children aged 0-59 months shows the percentage of malnutrition is 3.4% and under nourished is 14.4% (depkes.go.id, 2018). One of the effects of malnutrition is the occurrence of grow short in children or often referred to as stunting. In 2017 22.2% or around 150.8 million toddlers in the world were stunted. The aim of the implementation of the community service program was to develop the welfare section, namely the productivity of the culinary business a manufacture of processed mackerel and soybean through nutrition education to prevent stunting and increase the family economy. The methodology used in this community service program are planning and training productive community partnership programs. The mechanisms for implementing this activity are present material content, and indirect practice. Community service activities that have been carried out in Benda Baru, Pamulang, South Tangerang has been conducted online. The results obtained from the community service program based on of knowledge aspect, there was an increase with a difference of 32.2 obtained from the result of the pre-test and post-test and having skills on several examples of processed food products made from mackerel and soybean which contain high protein to prevent stunting. Abstrak Angka gizi buruk di Indonesia terhitung tinggi menurut hasil Pemantauan Status Gizi (PSG) yang dilakukan Kementerian Kesehatan tahun 2016, status gizi balita usia 0-59 bulan menunjukkan persentase gizi buruk sebesar 3,4% dan gizi kurang sebesar 14,4% (depkes.go.id, 2018). Salah satu dampak dari kekurangan gizi adalah terjadinya tumbuh pendek pada anak atau sering disebut dengan stunting. Tahun 2017, 22,2% atau 150,8 juta balita di dunia mengalami stunting. Tujuan dari pelaksanaan program PPM (Pengabdian Pada Masyarakat) ini adalah mengembangkan bidang kesejahteraan yakni produktivitas usaha kuliner berbahan dasar ikan kembung dan kacang kedelai melalui edukasi gizi pencegahan stunting serta dapat menambah perekonomian keluarga. Metodologi yang digunakan pada program PPM ini adalah perencanaan dan pelatihan program kemitraan masyarakat produktif. Mekanisme pelaksanaan kegiatan ini adalah pemberian materi, dan praktek online. Kegiatan PPM yang telah dilaksanakan di Kelurahan Benda Baru, Pamulang, Tangerang Selatan ini telah dilakukan secara online. Hasil yang diperoleh dari program PPM berdasarkan aspek pengetahuan, terjadinya peningkatan dengan selisih 32,2 yang diperoleh dari hasil pre test dan post test serta mempunyai keterampilan tentang beberapa contoh produk olahan makanan berbahan dasar ikan kembung dan kacang kedelai yang mengandung protein tinggi untuk mencegah stunting.